Pedicle Morphometry of Subaxial Cervical Spine Using Computed Tomography Scans among Adult Ugandan Subpopulation - Ssebuggwawo Jonathan; Wani Muzeyi; Erem Geoffrey; Waiswa Gonzaga; Ssekitooleko Badru; Kajja Isaac (International Journal of Biomedical Imaging)
Background. Accurate placement of pedicle screws in the subaxial cervical spine requires precise understanding of vertebra anatomy. Little is known about the morphometric characteristics of the subaxial cervical pedicle in the Ugandan population. The objective of the study was to determine the morphometric dimensions of pedicles in the subaxial cervical spine among the adult Ugandan population. Methods. We conducted a cross-sectional study from March to November 2019 among adult Ugandans with a normal cervical CT scan at Nsambya hospital in Kampala. Eligible participants were consecutively recruited into the study. Data on baseline characteristics and pedicle dimensions from the CT scan finding was collected using a structured questionnaire. Data was analysed using Stata 13.0. Pedicle dimensions for the different levels of subaxial cervical vertebrae were summarised as means and standard deviations, the Mann–Whitney test was used to compare pedicle dimensions for the different vertebra levels among females and males on both right and left sides, and the level of significance was set at 0.05. Results. A total of 700 subaxial cervical pedicles (C3-C7) from 49 males and 21 female participants were studied. Pedicle width diameter showed cephalocaudal gradual increment from C3 1.65(0.63) mm to 3.46(0.75) mm at C7. Pedicle height also showed an increase caudally with smallest diameter at C3 (1.98(0.76) mm) and largest at C5 in females (3.67(6.42) mm) and at C7 in males (3.83(0.76) mm). The pedicle height was wider than the pedicle width at all levels. The pedicle chord length gradually increased caudally in both sexes ranging from 29.08(1.35) mm at C3 to 32.53(3.19) mm at C7. The axial angles were oriented medially and showed no consistent trend ranging between 50° and 53°. The sagittal angles decreased as one moved from C3 to C7. The dimensions of females were significantly smaller than in males. Conclusion. Pedicle endosteal width was smaller than pedicle height dimensions at all levels. Pedicle cord length increased caudally. The pedicle dimensions, except angulations, were smaller in females than in males.